First-in-human evaluation of memory-like NK cells with an IL-15 super-agonist and CTLA-4 blockade in advanced head and neck cancer - Roman M. Shapiro; Michal Sheffer; Matthew A. Booker; Michael Y. Tolstorukov; Grace C. Birch; Moshe Sade-Feldman; Jacy Fang; Shuqiang Li; Wesley Lu; Michela Ansuinelli; Remy Dulery; Mubin Tarannum; et al. (Journal of Hematology & Oncology)
Abstract Background Cytokine induced memory-like natural killer (CIML NK) cells combined with an IL-15 super-agonist (N-803) are a novel modality to treat relapsed/refractory head and neck cancer. Methods We report data from a phase I trial of haploidentical CIML NK cells combined with N-803 with or without ipilimumab (IPI) in relapsed/refractory head and neck cancer patients after a median of 6 prior lines of therapy. The trial adhered to a 3 + 3 dose de-escalation design, with primary endpoint being safety. High-resolution immunophenotypic and transcriptional profiling characterized the NK cells and their interacting partners in vivo. Results The primary safety endpoint was established, with dose-limiting toxicity in 1/10 patients. A transient disease control rate correlated with donor NK cell expansion, the latter occurring irrespective of IPI. The combination of CIML NK cells with N-803 and IPI was associated with increased early NK cell proliferation, contraction of Treg: Tcon, rapid recovery of recipient CD8+ T cells, and subsequent accelerated rejection of donor NK cells. Conclusions CIML NK cells combined with N-803 and ipilimumab to treat head and neck cancer is safe, and associated with a more proliferative NK cell phenotype. However, the combination leads to reduced HLA mismatched NK cell persistence, resulting in an important limitation affecting NK cell combination therapies in clinical trials. These results inform evaluation of CIML NK therapy for advanced malignancies, with considerations for combination with IPI. Trial Registration NCT04290546.